Epidemiology of travelers' diarrhea in Thailand - Virasakdi Chongsuvivatwong (2018)
Background Current data on risk of travelers' diarrhea (TD) among visitors to Thailand largely comes from US military personnel, Peace Corps volunteers, or expatriates. We performed a 14-month systematic study of the incidence rate and characteristics of TD and a smaller study of etiology of the disease among visitors to Phuket and Chiang Mai. Methods One randomly selected day each week from August 2005 until October 2006, data were collected from foreign tourists departing from airports serving Phuket and Chiang Mai. A separate subgroup of subjects with TD acquired in Phuket were invited to submit a stool sample for enteropathogens. Results Based on 22,401 completed questionnaires, the attack rate for TD was highest among residents from Australia or New Zealand (16%), while those from the United States and Europe had attack rates of 7% to 8%. Independent risk factors for the development of TD were eating outside the hotel and eating meat. In contrast, a history of drinking tap water and consuming ice cream were protective. In 56 subjects studied for etiology, Aeromonas spp were found in 8 subjects (14%), enterotoxigenic Escherichia coli (ETEC) or Vibrio spp each was found in 7 (13%) with O1 V. cholera (cholera) seen in one, mixed pathogens were found in 3 (5%), with no pathogen being detected in 33 (59%). Conclusions Phuket and Chiang Mai should not be considered high-risk destinations for development of TD among US and European travelers to Thailand. In the study, Aeromonas, ETEC, and Vibrio spp were the most frequent enteropathogens identified. © 2009 International Society of Travel Medicine.